THE IMPORTANCE OF DEVELOPING PROFESSIONAL COMPETENCIES IN THE STUDY OF ENGLISH BY STUDENTS OF THE NON-PHILOLOGICAL FACULTY - Tursunboyeva Mukhlisa Anvar kizi (American Journals, 2024)
This article describes the importance of developing the professional competencies of students of the non-philological faculties of a higher educational establishments in English lessons. On this topic, the scientific studies and opinions of a number of scientists are indicated, and the necessary conclusions are also presented.
Keywords: competence, professional competence, linguistics, individual creativity, pedagogical activity, integral competence.